-4(c-24)=-4c-24

Simple and best practice solution for -4(c-24)=-4c-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(c-24)=-4c-24 equation:


Simplifying
-4(c + -24) = -4c + -24

Reorder the terms:
-4(-24 + c) = -4c + -24
(-24 * -4 + c * -4) = -4c + -24
(96 + -4c) = -4c + -24

Reorder the terms:
96 + -4c = -24 + -4c

Add '4c' to each side of the equation.
96 + -4c + 4c = -24 + -4c + 4c

Combine like terms: -4c + 4c = 0
96 + 0 = -24 + -4c + 4c
96 = -24 + -4c + 4c

Combine like terms: -4c + 4c = 0
96 = -24 + 0
96 = -24

Solving
96 = -24

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8x+6+7x-3=108 | | -2f+7f=29 | | 2(4x+3)-2=x+20 | | 9x+5=8x-6 | | -27=-7(3b-8) | | 2h-4x=13 | | M+4m=-15 | | 2x^2+x=180 | | E=8b+12nforb | | -23=2n-7n | | 4x-2h=13 | | -18x-24=-9x+3 | | 3(5+7p)=120 | | (6x^3-4)+(2x^3+9)= | | -2(9d-8)=34+6d | | -b-4+3b=3+b | | X+17=3x-23 | | 5x+2y^3+xy^2=0 | | 8x+11-6x=5(x+7) | | 5x+2x-8=13 | | 4y-13=23# | | 48t-33=51t-69 | | -3(10)+9=-21 | | -98=2(-7+7x) | | 8(6-7y)=26 | | -3-6n=-3(1+4n)+6n | | 4x+24=8x-12 | | 1.2d-6= | | 18=28+4(-5) | | 4x+7x+8+7x+2=172 | | -5n-5(-8n+3)=13+7n | | -7-4x=2x-7(1-7x) |

Equations solver categories